Diffusion of China's Community Health Management Policies: an Analysis Using Diffusion of Innovation Theory - Hang XU, Xiaojing MA, Tao DAI (Zhongguo quanke yixue, 2022)
Background All levels of China gevernment departments have attached importance to community health management services, an important way for disease prevention and resident saveealth improvement, and successively promulgated relevant management policies. However, there is a lack of systematic review and research on the diffusion paths and characteristics of these policies, which are still unclear due to the diversity of promulgating agencies and types of polices. Objective To explore the process and features of the diffusion of China community health management policies, providing a reference for the formulation and promotion of these kinds of policies. Methods From June to September 2021, we searched policy documents related to community health management services published from January 1997 to September 2021 in the official websites of all levels of government and health administrative departments, as well as authoritative databases such as PKULAW.com and so on, then quantitatively analyzed the process and features of diffusion of them in terms of four aspects (intensity, breadth, speed, and direction of diffusion) using policy network analysis and keyword analysis by time series. Results A total of 1 540 policies related to community health management were retrieved (including 159 central policies and 1 381 local policies) . The development of community health management services in China may be divided into five stages: germination (1997—2004) , formation (2005—2008) , transition (2009—2012) , initial development (2013—2015) and innovation and development (2016—2021) . Policies which were diffused more intensively and widely were promulgated by central agencies of higher administrative levels, and mainly classified as planning, opinions, and laws. The absolute diffusion breadth of the top 10 policies in terms of diffusion intensity exceeded 30, and the absolute diffusion breadth of the top 10 policies in terms of spreading breadth exceeded 20. The diffusion speed of most policies showed a trend of first increasing and then slowing down over time. The diffusion of Chinese medicine health management policies mainly presented parallel diffusion among policy promulgating agencies at the same level, and top-to-bottom diffusion from the central policy promulgating agencies to the local ones. Conclusion Through policy diffusion research, we had a comprehensive understanding of the process and characteristics of diffusion of China's community health management policies, and drew a number of conclusions, including the five-stage development of these policies, and the policy diffusion process may be affected by the attributes of the administrative level of the promulgating agencies and types of policies. In addition, the diffusion of these policies could be achieved via multiple paths, with many mechanisms of action such as learning and imitation, with a speed of "first increasing, then slowing down" over time.